Hepatitis A virus antibody among 0 - 60 years residents in Fujian province ten years after vaccination program: analysis on serological surveillance data of 2009 and 2019 - Suhan ZHANG; Xiuhui YANG; Hairong ZHANG; Zhifei CHEN (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo examine the effect of hepatitis A virus (HAV) vaccine vaccination on serum HAV antibody level 10 years after HAV vaccine being included into the national Expanded Programme on Immunization (EPI) among the residents in Fujian province for providing evidence to prevention and control of viral hepatitis A.MethodsWe collected blood samples among 4 827 residents aged 0 - 60 years recruited with stratified random cluster sampling in 10 municipalities/prefectures across Fujian province from December 2018 through March 2019. Serum HAV immuno-globulin G (HAV-IgG) of the participants were detected with enzyme-linked immunosorbent assay (ELISA) and compared with those among healthy residents of same age groups in 2009.ResultsThe positive rate of HAV-IgG was 96.86% for all the participants, which was significantly higher than that (49.51%) for the healthy residents aged 0 - 60 years in 2009. Unsignificantly increased serum HAV-IgG positive rate was detected among 20 - 50 years-old childbearing women in comparison to that among the childbearing women of same ages in 2019 (96.73% vs. 83.14%); the positive rate was also increased in the participants less than one year old in contrast to the infants of same age in 2009 (96.76% vs. 32.37%). In the participants aged 1 - 15 years old, the standardized HAV vaccine vaccination rate was 86.06% and significantly higher than that (46.47%) in the residents of same ages in 2009.ConclusionThe positive rate of serum HAV-IgG increased significantly among 0 - 60 years old residents and the HAV-IgG content remained at a relatively high level in the infants less than one year old in 2019, ten years after HAV vaccine being included into EPI in Fujian province.